2013
DOI: 10.1371/journal.pone.0067978
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness: Its Correlates and Association with Health Behaviours and Outcomes in Nine Countries of the Former Soviet Union

Abstract: BackgroundResearch suggests that the prevalence of loneliness varies between countries and that feeling lonely may be associated with poorer health behaviours and outcomes. The aim of the current study was to examine the factors associated with loneliness, and the relationship between feeling lonely and health behaviours and outcomes in the countries of the former Soviet Union (FSU) – a region where loneliness has been little studied to date.MethodsUsing data from 18,000 respondents collected during a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
117
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 55 publications
14
117
1
5
Order By: Relevance
“…More research is needed in order to determine causal factors underlying the association between loneliness and cognitive functioning (Boss et al 2015). Further, as found in a number of previous studies (Cacioppo et al, 2002;Cohen-Mansfield et al, 2016;Hawkley & Cacioppo, 2010;Petitte et al, 2015;Stickley et al, 2013), this study found that loneliness was associated with poor subjective health status.…”
Section: Discussionsupporting
confidence: 50%
“…More research is needed in order to determine causal factors underlying the association between loneliness and cognitive functioning (Boss et al 2015). Further, as found in a number of previous studies (Cacioppo et al, 2002;Cohen-Mansfield et al, 2016;Hawkley & Cacioppo, 2010;Petitte et al, 2015;Stickley et al, 2013), this study found that loneliness was associated with poor subjective health status.…”
Section: Discussionsupporting
confidence: 50%
“…This suggests that a lack of financial resources may constrain some individuals from fully participating in society, which may lead to loneliness and social isolation among those who are already at risk via a number of different pathways, including poor health and widowhood. However, research comparing the association between wealth and loneliness across nine countries of the Former Soviet Union found that wealth was only related in three of the countries studied (Stickley et al, 2013). This suggests that wider political or cultural factors may be involved, similar to other outcomes, such as wellbeing and quality of life (Niedzwiedz et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Using population level data we can also explore variations in loneliness between countries. Stickley et al [9] described high levels of loneliness in the countries of the former Soviet Union whilst Sundstrom et al [10] compared loneliness within Europe and reported the "northsouth" divide with levels of loneliness markedly higher for older people in southern countries as compared with northern Europe [11]. Yang and Victor [6] between countries and over time.…”
Section: Introductionmentioning
confidence: 99%